Infection Kinetics and Tropism of Borrelia burgdorferi sensu lato in Mouse After Natural (via Ticks) or Artificial (Needle) Infection Depends on the Bacterial Strain - Sertour, Natacha; Cotté, Violaine; Garnier, Martine; Malandrin, Laurence; Ferquel, Elisabeth; Choumet, Valérie (Frontiers in Microbiology, 2018)
Borrelia burgdorferi sl is a complex of pathogen bacteria transmitted to the host by Ixodes ticks. European Ixodes ricinus ticks transmit different B. burgdorferi species, pathogenic to human. Bacteria are principally present in unfed tick midgut, then migrate to salivary glands during blood meal and infect a new host via saliva. In this study, efficiency of transmission in a mouse model of three pathogen species belonging to the B. burgdorferi sl complex, B. burgdorferi sensu stricto (B31, N40 and BRE-13), B. afzelii (IBS-5) and B. bavariensis (PBi) is examined in order to evaluate infection risk after tick bite. We compared the dissemination of the Borrelia species in mice after tick bite and needle injection. Location in the ticks and transmission to mice were also determined for the three species by following infection kinetics. After inoculation, we found a significant prevalence in the brain for PBi and BRE-13, in the heart, for PBi, in the skin where B31 was more prevalent than PBi and in the ankle where both B31 and N40 were more present than PBi. After tick bite, statistical analyses showed that BRE-13 was more prevalent than N40 in the brain, in the bladder and in the inguinal lymph node. When Borrelia dissemination was compared after inoculation and tick bite, we observed heart infection only after tick inoculation of BRE-13, and PBi was only detected after tick bite in the skin. For N40, a higher number of positive organs was found after inoculation compared to tick bite. All European B. burgdorferi sl strains studied were detected in female salivary glands before blood meal and infected mice within 24H of tick bite. Moreover, Borrelia-infected nymphs were able to infect mice as early as 12 hours of tick attachment. Our study shows the need to remove ticks as early as possible after attachment. Moreover, Borrelia tropism varied according to the strain as well as between ticks bite and needle inoculation, confirming the association between some strains and clinical manifestation of Lyme borreliosis, as well as the role played by tick saliva in the efficiency of Borrelia infection and dissemination in vertebrates.